Sistem Informasi Pengolahan Zakat Fitrah Pada Masjid Amaliyah Desa Pulo Jantan Berbasis Framework Codeigniter - Anggryani, Vidya (Journal of Computer Science and Information System(JCoInS), 2022)
Zakat Fitrah is one of the services carried out by Muslims contained in the pillars of Islam which is a cleanser himself and is his responsibility to eliminate the sins that occur during fasting during the month of Ramadan. In the processing of zaktat fitrah the most in the spotlight is Amil Zakat. Amil Zakat is people who are in charge of handling the distribution of zakat or assigned to distribute zakat to groups who are entitled to receive zakat.If amil is negligent and inaccurate in managing zakat, it may be that the distribution of zakat is not on target.Masjid Amaliyah in Pulo Jantan Village is one of the places for collecting zakat fitrah funds, but in processing the data it still uses manual methods, so the data that has been stored will be easy and risk of being lost or damaged and in processing the zakat fitrah also takes a very long time.To overcome this problem, a zakat fitrah zakat processing information system is designed which can be used in zakat fitrah processing. In making this zakat fitrah processing information system using the waterfall method, where this method begins with planning (modeling), modeling (modeling), construction (construction), and the delivery of the system to the user.